2015
DOI: 10.1021/acs.analchem.5b01535
|View full text |Cite
|
Sign up to set email alerts
|

Sensitive Fluorescence Probe with Long Analytical Wavelengths for γ-Glutamyl Transpeptidase Detection in Human Serum and Living Cells

Abstract: A new sensitive fluorescent probe with long analytical wavelengths for γ-glutamyl transpeptidase (GGT) assay has been developed by incorporating the γ-glutamyl group as a recognition unit into the fluorophore of cresyl violet (CV). The detection mechanism is based on the GGT-catalyzed cleavage of the γ-glutamyl group, followed by the release of CV, which leads to a distinct color change from light yellow to pink and a large fluorescence enhancement at 615 nm (λex = 585 nm). Under the optimized conditions, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
67
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 86 publications
(68 citation statements)
references
References 42 publications
1
67
0
Order By: Relevance
“…In 2015, Ma and co‐workers took the widely used fluorophore of Cresyl Violet to design a sensitive off–on fluorescence probe ( 7 ), which showed a significant (ca. 500‐fold) fluorescence enhancement at λ =615 nm ( λ ex =585 nm) upon reaction with GGT . Studies on the detection sensitivity toward GGT revealed that 7 was highly sensitive to detect GGT, with a detection limit of 5.6 mU L −1 GGT.…”
Section: Activatable Fluorescence Probes For Ggtmentioning
confidence: 99%
“…In 2015, Ma and co‐workers took the widely used fluorophore of Cresyl Violet to design a sensitive off–on fluorescence probe ( 7 ), which showed a significant (ca. 500‐fold) fluorescence enhancement at λ =615 nm ( λ ex =585 nm) upon reaction with GGT . Studies on the detection sensitivity toward GGT revealed that 7 was highly sensitive to detect GGT, with a detection limit of 5.6 mU L −1 GGT.…”
Section: Activatable Fluorescence Probes For Ggtmentioning
confidence: 99%
“…[13][14][15][16][17][18][19][20] In the past several years, a number of fluorescence probes were developed to detect ONOOby usually taking advantage of the strong oxidizability and nucleophilicity of ONOO -. They mainly include the phenyl boronic ester-based, 21,22 hydrazine-based, 23,24 selenium or tellurium-based [25][26][27] and methyl(4hydroxyphenyl)amino-based probes.…”
Section: Introductionmentioning
confidence: 99%
“…In order to visualize GGT activity in living samples, several GGT-activatable fluorescent probes have been developed x,y . Among these probes, we focused on our previously developed γ-glutamyl hydroxymethyl rhodamine green (gGlu-HMRG), which enables in vivo identification of cancer tissues 11, 12 . gGlu-HMRG is nonfluorescent in its native state but is rapidly hydrolyzed by GGT to generate HMRG, which emits fluorescence with a peak wavelength of ~520 nm 12 .…”
Section: Introductionmentioning
confidence: 99%